1992
DOI: 10.1111/j.1445-5994.1992.tb02144.x
|View full text |Cite
|
Sign up to set email alerts
|

The value of complement measurements in the assessment of lupus activity

Abstract: The complement system was studied prospectively in 29 patients, predominantly renal (25), with systemic lupus erythematosus (SLE) to examine the value of complement assays in the distinction between active and inactive disease. Disease activity was evaluated primarily by clinical, biochemical and histological parameters which were obtained at the time of assessment. Fourteen patients had active disease, as assessed by clinical and laboratory criteria. C1q, C4, C4a, C2, C3, C3a, C5, total haemolytic activity (C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1996
1996
2006
2006

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…A total of 50 publications were identified that contained information on C3 in apparently healthy individuals . Thirty-six articles had enough data to calculate central estimates (8,9,(11)(12)(13)(14)16,17,19,20,(22)(23)(24)26,28,29,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)44,46,48,49,(52)(53)(54)(55)(56). Eighteen studies supplied sufficient information for calculating the reference intervals (8,10,11,13,14,17,(21)(22)(23)(24)27,37,40,49,…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A total of 50 publications were identified that contained information on C3 in apparently healthy individuals . Thirty-six articles had enough data to calculate central estimates (8,9,(11)(12)(13)(14)16,17,19,20,(22)(23)(24)26,28,29,(32)(33)(34)(35)(36)(37)(38)(39)(40)(41)(42)44,46,48,49,(52)(53)(54)(55)(56). Eighteen studies supplied sufficient information for calculating the reference intervals (8,10,11,13,14,17,(21)(22)(23)(24)27,37,40,49,…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…A total of 32 publications were identified that contained information on C4 in apparently healthy individuals (7,(9)(10)(11)(12)16,17,19,20,(22)(23)(24)(25)(26)(27)(28)(29)(30)32,(34)(35)(36)(37)(38)(40)(41)(42)(43)(44)(45)(46)(47)(49)(50)(51)(52)(53)(54)(55), and supplied sufficient information for calculating central estimates (9,11,12,16,17,19,20,22-24, 26-29, 32,34-38,40-42,44,46,47,49,51-55). Thirteen articles supplied sufficient information for calculating the reference intervals (20,(22)(23)(24)27,28,30,40,49,…”
Section: Number Of Studies Available For Analysismentioning
confidence: 99%
“…In fact, CP lytic activity, usually evaluated by measurement of CH50 units and the concentrations of C3, C4 and factor B, are the only complement parameters available in many laboratories. Furthermore, the usefulness of measuring C3 and C4 levels to assess disease activity in patients with systemic lupus erythematosus has recently been highlighted (17,(19)(20)(21).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to C9, earlier components of the complement cascade such as C3 and C4 tend to be in reduced concentration in the presence of a pathological activator such as antigen/antibody complexes [10,11]. Previous studies have shown that several mechanisms underlie this reduced concentration.…”
Section: Introductionmentioning
confidence: 97%